Alicia Eguren: beyond the militant couple (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2024)
This paper seeks to account for the political and intellectual agency of Alicia Eguren by analysing her personal correspondence and her press interventions during the 1970s. This approach allows us to reflect on the limitations of the use of the category of "militant couple" to explore the evolution of this referent of the Peronist left, while proposing to recover her political proposals in the context of the end of the proscription of Peronism. This proposal also makes it possible to recover the future projects thought and projected by Eguren for revolutionary Peronism.